Truth, Deception, and Coercion; Communication Strategies Used by Caregivers of Children with Perinatally Acquired HIV During the Pre-Disclosure and Post-Disclosure Period in Rural Communities in South Africa - Mmathale Molokwane MPH; Sphiwe Madiba DrPH (SAGE Publishing, 2021)
Typically, children with perinatal HIV (PHIV) receive antiretroviral treatment (ART) for a long time prior to receiving disclosure. Communication with children about HIV and treatment is critical for monitoring adherence and retention in care. However, there is a dearth of information on communication between caregivers and their children. This study examines what and how caregivers tell their their children about their illness and medication in the pre-disclosure and post-disclosure period. A qualitative study using semi-structured one-on-one interviews and focus group discussions was conducted with caregivers recruited via purposive sampling from a rural sub-district in South Africa. The interviews were analyzed using thematic analysis. The sample consisted of 38 caregivers, 24 of whom were the children's biological mothers, 20 had disclosed to the children and 18 had not done so. Caregivers who had disclosed had told their children the truth and named the disease as HIV, but communication about HIV was infrequent and focused on pill taking. Those who had not disclosed had lied, deflected illness-related information, and attributed the children's ill health to co-morbid conditions. To enforce adherence, most caregivers used coercion and threats of the grave consequences of non-adherence as a communication strategy. Those who had not disclosed used deception, deflecting, and coercion as strategies for coping through the pre-disclosure period. There is a need for healthcare workers to prepare, support, and empower caregivers to develop appropriate responses to children's questions and to understand the implications of deception on future full disclosure and children's acceptance of their HIV status.